Our lost declaration : America's fight against tyranny from King George to the deep state - Lee, Mike, 1971- (Sentinel, 2019)
"Bestselling author and respected conservative Senator Mike Lee sheds new light on America's Declaration of Independence--and explains its relevance in the fight against big government today. Most Americans are familiar with the Constitution as an outline of for limited government. Few, however, understand how significant the Declaration of Independence was as an initial blow in the war against government encroachment. A champion of limited government, Senator Lee reinterprets the inspiring story of the colonists who fought the tyranny of King George, and shows how we find ourselves facing similar obstacles today: presidents who fail to enforce the law, a massive regulatory state, and a creeping centralization of power. In the thrilling style of his bestsellers OUR LOST CONSTITUTION and WRITTEN OUT OF HISTORY, Senator Lee makes history come alive to educate, entertain, and rally all patriots who care about the survival of liberty in America"--